A novel collaborative study of abnormal roof water inrush in coal seam mining based on strata separation and wing crack initiation. (December 2022) - Wang, Zaiyong; Zhang, Qi; Zhang, Wenquan
Highlights: In this work, the process of water inrush due to roof bed separation was studied by similar simulation experiment and analytical wing crack initiation condition. New maximum tangential tensile stress (MTTS) criterion, maximum shear stress magnitude (MSSM) criterion, and minimum J2 criterion by considering T-stress at the crack tip were proposed. The experiment could reveal the evolution law of bed separation space, the process of water accumulation in the bed separation space, and the breaking characteristics of separation water inrush. Our analytical solution of wing crack initiation angle is approximately consistent with the experimental observation after water injection. The consistency between the similar experiment and the field result was illustrated. Abstract: Separation water inrush poses a potential threat to safe mining on the working face, whose mechanism should be investigated in order to take better prevention and control measures. In this study, aiming at the problem of separation water inrush under hydrostatic pressure, the 21805 working face of the Yushujing coal mine was chosen as the research object to establish an in-house similar simulation experiment. The experiment could reveal the evolution law of bed separation space, the process of water accumulation in bed separation space, and the breaking characteristics of separation water inrush. Meanwhile, in order to theoretically interpret the evolution of water-conducting fractured zone (WCFZ), an analytical model for wing crack initiation from compression-shear fracture and tension-shear fracture that considers T-stress was derived. The analytical model comprehensively considers the effects of overlying strata load and aquifer water pressure, fracture geometry, and rock properties. The results show that the time of separation water inrush obtained by the similar simulation experiment is consistent with the field result, and the orientation of new cracks generated due to water injection also coincides with the analytical solution. In addition, it is found that the development of bed separation space is a long-term process, which can provide a theoretical basis for the prevention and control of separation water inrush.